Prioritizing safety training for a more personal compliance of a safe and healthy work environment among students and staff of higher education institutions of Selangor - Kumarasamy, Mokana Muthu; Saad, Mazni; Abdul Rauf, Reeny Karlina; Mohamed Mohan, Noor Malinda; Ong, Mohd Hanafi Azman (2018)
Safety is an important element in an organization. A safe work space makes safety a priority throughout the organization. Improved safety will minimize job accidents, injuries, medical illnesses and death. Occupational safety and health (OSH) training that is provided by the top management of universities will create a safe and comfortable environment for both the staff and students. It also guarantees that every em-ployee is safe in the workplace. Thus, the primary objective of this study is to investigate the effect of safety training towards personal com-pliance. A total of 234 questionnaires were distributed to 20 higher educational institutions in Selangor, Malaysia. A conclusion was reached once the data were analyzed using SPSS; that safety training (B = 0.364, t = 11.90, p <.01) significantly has a positive effect on Personal Compliance.